THE EFFORTS TO IMPROVE QUALITY OF PUBLIC SERVICES IN IMPLEMENTING MOTOR VEHICLE TESTING : A CASE STUDY AT TRANSPORTATION OFFICE OF SUKABUMI CITY - NUKE NURULAINI; IKE RACHMAWATI; SAKTI ALAMSYAH (CV KULTURA DIGITAL MEDIA, 2021)
The Technical Implementation Unit of Motor Vehicle Testing (UPT PKB) of the Sukabumi City Transportation Service, as a vehicle testing service, has experienced many interactions between the quality of services provided and the level of community satisfaction, namely the process of how the government can provide the best services that are proportional to the value and costs that have been incurred. public vehicle owners are required to test. Excellent service is an agency's concern for customers by trying to provide the best possible service in meeting customer expectations and needs, based on service standards and procedures to realize customer trust. This study uses a case study approach to examine the 'how' and 'why' of services at the UPT PKB of the Sukabumi City Transportation Service. Attitudes, attention, actions, abilities, appearance, and responsibilities have been shown and displayed by the test officer. Efforts to improve services and overcome obstacles in service have also been carried out, but are hampered by the refocusing of the spending budget to overcome COVID-19.